Provisional Growth Estimate of Pterocarpus dalbergioides (Andaman Padauk) - Singh, S. P.; Sharma, R. S.; Singh, Jai (Indian Forester, 1984)
Information on growth of Pterocarpus dalbergioldes (Andaman padauk) is scanty and no attempt was to estimate period of harvest for this species. Though the growth data is limited, yet attempt is made to study its growth pattern and project the same in the form of yield table.